Effects of a Comprehensive Performance Improvement Strategy on Postoperative Adverse Events in Head and Neck Surgery. (May 2019) - Panuganti, Bharat; Qiu, Yuqi; Messing, Barbara; Lee, Gregory; Fakhry, Carole; Blanco, Raymond; Ha, Patrick; Messer, Karen; Califano, Joseph A.
Objectives: We aimed to demonstrate the efficacy of a multifaceted performance improvement regimen to reduce the incidence of adverse events following a spectrum of head and neck surgical procedures. Methods: We conducted a chart review of patients who underwent a head and neck procedure between January 1, 2013, and October 30, 2015, at our institution, including 392 patients (450 procedures) before the quality improvement regimen was implemented (October 1, 2013) and 942 patients (1136 procedures) after implementation. Multivariate statistical models were used to investigate the association of clinical parameters and the intervention with postoperative adverse event rate. Results: The incidence of adverse events decreased from 12.9% to 7.2% (95% CI, 2.46%-9.38%) after the intervention. Male sex (adjusted odds ratio [ORadj] = 1.57; 95% CI, 1.06-2.31) and the intervention (ORadj = 0.51; 95% CI, 0.35-0.74) were predictive of overall adverse event incidence by univariate and multivariate analyses. Although patient comorbid status, quantified with the Charlson Comorbidity Index, was not found to affect overall adverse event risk, each 1-point increase in index score was associated with a 17% relative increase (ORadj = 1.17; 95% CI, 1.03-1.33) in the odds of a high-grade adverse event. Discussion: Comprehensive performance improvement programs can improve perioperative adverse event risk in head and neck surgery. Patient comorbid status and sex are considerations during assessment of the likelihood of high-grade and overall adverse event risk, respectively. Implications for Practice: Given the cost of surgical complications, a comprehensive approach to perioperative risk mitigation is warranted.